Downton Abbey. Season 1 [videorecording (Blu-Ray)] - Fellowes, Julian; Trubridge, Liz; Bonneville, Hugh; Findlay, Jessica Brown, 1989-; Carmichael, Laura, 1986-; McGovern, Elizabeth, 1961-; Carter, Jim, 1948-; Coyle, Brendan; Dockery, Michelle, 1981-; Doyle, Kevin, 1961-; Finneran, Siobhan, 1967-; Froggatt, Joanne, 1980-; et al. (PBS Distribution, 2013)
"This set includes the first three seasons of this Golden Globe and multi-Emmy Award-winning series, bringing Downton Abbey from pre-war England through the storms of World War I and into the social upheaval of England in the 1920s as the lives of its inhabitants are shaped by romance and heartbreak, ambition and betrayal."-- container